The Impact Of Technology Advancement On Analogue Screen Printing In Kuching - Shannon Ann, Ricky (Universiti Malaysia Sarawak (UNIMAS), 2020)
This research sought to describe the impact of technology advancement on analogue screen printing in Kuching. With technology becoming increasingly dominant in society and in the printing industry, the process and methods of analogue screen printing have changed due to innovations and developments of technology. The implication of technology advances has as well gradually affected local printers and practitioners of analogue screen printing in Kuching. Therefore, the purpose of this study is to analyze the impact and implications of technology is having on analogue screen printing, to identify the factors contributed in affecting the utilization of analogue screen printing in Kuching and to understand the differences between both analogue and digital printing. By using qualitative analysis throughout this research, this will provide an in-depth understanding of the technological impacts on analogue screen printing and the factors which have affected the utilization of analogue screen printing in the printing industries Hence, this study may broaden the understanding between digital and analogue screen printing among local printing firms in Kuching and enhances the concept and understanding of analogue screen printing application among Kuching’s local printing firms and its customers in Kuching.